Improving asthma care in children: revealing needs and bottlenecks through in-depth interviews - Casper E. W. Gijsen; Carolien van Rossem; Jean W. M. Muris; Marieke W. P. van Horck; Edward Dompeling (npj Primary Care Respiratory Medicine)
Abstract Asthma affects 7% of Dutch children and poses an increasing challenge, highlighting the need for effective paediatric asthma care. Achieving optimal asthma control is crucial given the potentially negative long-term effects of bad asthma control on lung development and quality of life in young children. The aim was to understand the challenges and requirements of existing asthma management practices in children. In a qualitative explorative study design, semi-structured, in-depth interviews were held among 37 Dutch stakeholders. A total of 15 patients/parents, 10 general practitioners (GPs), 5 paediatricians/paediatric pulmonologists and 7 nursing specialist/pulmonary nurses participated. Analysis was based on a thematic inductive analysis, using open and axial coding. GPs tended to emphasise the treatment of patients/parents with acute symptoms and underestimate the diagnosis and management of chronic symptoms, leading to possible over- and undertreatment. Asthma care between primary and secondary healthcare is fragmented and worsens these challenges. Moreover, the absence of well-established follow-up structures in primary care contributes to insufficient self-management skills among patients. Shared Decision-Making in children lacks a tailored approach, with variable engagement levels among healthcare providers. Limited focus on preventive strategies leads to little attention to, for example, promoting healthy lifestyles. Moreover, children are often not actively involved in decision-making. The study provides valuable insights to improve the quality and continuity of care for children with asthma and their parents. It underlines the need for a comprehensive and integrated care pathway to minimise the long-term negative effects of uncontrolled asthma.